Short Communication: Second record of Eumops chiribaya (Chiroptera, Molossidae) in Peru - CÉSAR EDGARDO MEDINA; DARWIN RONALD DÍAZ; BRIAN ANDREW MALAGA; YASMY KARINA MEDINA; EVARISTO LÓPEZ (Society for Indonesian Biodiversity, 2018)
Medina CE, Díaz DR, Malaga BA, Medina YK, López E. 2018. Short Communication: Second record of Eumops chiribaya (Chiroptera, Molossidae) in Peru. Biodiversitas 19: 1979-1984. The bat Eumops chiribaya was recently described from southwestern Peru, based on unique specimen collected in the coastal desert of Moquegua Department. Herein, we document the second record for the country based on a specimen collected in Arequipa Department. This specimen is described in detail and compared with the holotype of E. chiribaya. This record represents a significant extension of the geographic range for this species, both in latitude and elevation, and it show the high diversity of bats living in the coastal valleys of southwestern Peru. Our record adds one genus and species to the Arequipa Department, totaling 17 bat species in the Department.